Transformasi Pedagogis Guru Pendidikan Agama Islam dalam Pembelajaran Berbasis Keadilan Gender dan Inklusivitas - Afnan Raodah; Dika Tripitasari; Ahdar Ahdar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This study examines the pedagogical transformation of Islamic Religious Education (PAI) teachers in realizing gender-equitable and inclusive learning. Ideal PAI teacher pedagogy encompasses not only content mastery but also pedagogical competence and social sensitivity capable of responding fairly to learner diversity. This study identifies that traditional teacher-centered, rote-oriented pedagogy with minimal gender awareness constitutes a primary barrier to creating equitable learning environments. The required transformation includes developing cooperative learning strategies, eliminating gender bias in classroom interactions, differentiating instruction according to student needs, and using inclusive stereotype-free teaching materials. The theological foundation of Islam affirms that human dignity regardless of gender as emphasized in QS. Al-Hujurat: 13 aligns with inclusivity values in education, making this transformation an authentic manifestation of the rahmatan lil'alamin principle rather than a deviation from Islamic values. Despite ongoing challenges including entrenched patriarchal culture, limited gender literacy, insufficient inclusive teaching materials, and social resistance, this pedagogical transformation carries broad implications for improving learning quality, strengthening tolerance, and enhancing PAI teacher professionalism in Indonesia.